Performance Evaluation of Different ToS Using Heterogeneous Communication Interfaces in FANETs - Ribeiro, Laura Michaella B.; Müller, Ivan; Becker, Leandro Buss (Frontiers in Future Transportation, 2022)
The use of different types-of-services (ToS) such as voice, data, and video are increasingly present in the execution of applications involving networks composed of multiple UAVs. These applications usually require UAVs to share different ToS in a dynamic way and in ad-hoc mode, so that they can support the execution of cooperative/collaborative tasks. The use of heterogeneous communication has showed gains in maintaining the connection among highly mobile nodes while increasing reliable transmission of data, as needed in MANETS, VANETs and, more recently in FANETs. The aim of this paper is to present a performance eveluation of an heterogeneous interface manager (IM) that applies a heuristic to choose the best among several singleband and multiband wireless communication interfaces: IEEE 802.11n, IEEE 802.11p, IEEE 802.11ac, and IEEE 802.11ax. Simulated scenarios with 3, 5, and 8 UAVs nodes were developed by integrating NS-3 and Gazebo simulation tools. The IM performance was analyzed by applying different amount of interfaces and by defining two set of results, composed by MAC and PHY metrics and applications metrics. Finally, the paper also evaluates performance considering voice, data, and video streaming type of services. The results showed that combination of different interfaces is very powerful to maintain or increase the communication intensity.